THE INFLUENCE OF TRANSGENERATIONAL SUCCESSION INTENTION ON SUCCESSION PLANNING: THE MODERATING ROLE OF RELATIONSHIP QUALITY BETWEEN FAMILY CEO AND SUCCESSOR - Humaidatul Abdillah; Metta Padmalia (International Journal of Economics, Business and Accounting Research (IJEBAR), 2026)
This study examines the effect of transgenerational succession intention on the level of succession planning in family businesses in Indonesia by incorporating the quality of the relationship between the family CEO and the successor as a moderating variable. Grounded in socioemotional wealth theory and relational systems theory, this research posits that the combination of an orientation toward preserving socioemotional wealth and a high-quality incumbent–successor relationship will foster more formal and structured succession planning. A quantitative approach is employed through a survey of members of the UC Family Business Community using purposive sampling of 200 respondents, with data collected via an online questionnaire using a five-point Likert scale and analyzed with PLS-SEM in SmartPLS. The findings show that all constructs exhibit adequate validity and reliability, and that both transgenerational succession intention and relationship quality have a positive and significant effect on the level of succession planning. Furthermore, high relationship quality strengthens the influence of transgenerational succession intention on succession planning, underscoring the importance of simultaneously managing transgenerational motivation and emotional professional relationships to ensure sustainable succession planning in family businesses.